Enzymatic synthesis of dimeric glycomimetic ligands of NK cell activation receptors - Drozdová, Anna; Bojarová, Pavla; Křenek, Karel; Weignerová, Lenka; Henssen, Birgit; Elling, Lothar; Christensen, Helle; Jensen, Henrik H; Pelantová, Helena; Kuzma, Marek; Bezouška, Karel; Krupová, Monika; et al. (Carbohydrate research, 2011)
This work reveals new structural relationships in the complex process of the interaction between activation receptors of natural killer cells (rat NKR-P1, human CD69) and novel bivalent carbohydrate glycomimetics. The length, glycosylation pattern and linker structure of receptor ligands were examined with respect to their ability to precipitate the receptor protein from solution, which simulates the in vivo process of receptor aggregation during NK cell activation. It was found that di-LacdiNAc triazole compounds show optimal performance, reaching up to 100% precipitation of the present protein receptors, and achieving high immunostimulatory activities without any tendency to trigger activation-induced apoptosis. In the synthesis of the compounds tested, two enzymatic approaches were applied. Whereas a β-N-acetylhexosaminidase could only glycosylate one of the two acceptor sites available with yields below 10%, the Y284L mutant of human placental β1,4-galactosyltransferase-1 worked as a perfect synthetic tool, accomplishing even quantitative glycosylation at both acceptor sites and with absolute regioselectivity for the C-4 position. This work insinuates new directions for further ligand structure optimisation and demonstrates the strong synthetic potential of the mutant human placental β1,4-galactosyltransferase-1 in the synthesis of multivalent glycomimetics and glycomaterials.
Keywords: Protein Binding; Biomimetics; Recombinant Proteins; mutace; vazebná místa; galaktosyltransferasy; molekulární mimikry; ligandy; beta-N-Acetylhexosaminidases; Antigens, CD; receptory buněk NK; CD antigeny; Pregnancy; Lymphocyte Activation; těhotenství; beta-N-acetylhexosaminidasy; Ligands; Placenta; diferenciační antigeny T-lymfocytů; Immunoprecipitation; polysacharidy; aktivace lymfocytů; Receptors, Natural Killer Cell; krysa rodu Rattus; rekombinantní proteiny; lektiny typu C; vazba proteinů; Binding Sites; placenta; Animals; lidé; Lectins, C-Type; ženské pohlaví; Humans; zvířata; buňky NK; Rats; biomimetika; imunoprecipitace; Polysaccharides; Mutation; Female; Antigens, Differentiation, T-Lymphocyte; Killer Cells, Natural; Galactosyltransferases; Molecular Mimicry